IMPLEMENTASI PENDIDIKAN KARAKTER BERBASIS TOLERANSI ANTAR UMAT BERAGAMA DI SMA MUHAMMADIYAH MAUMERE - Solo, Yuliana Dua; Rahardjanto, Abdulkadir (Program Studi Magister Pedagogi, 2016)
Abstract: This research aims to describe the implementation of character education based on a tolerance between religious communities conducted at Muhammadiyah Maumere High School. This research is a type of descriptive qualitative research on the implementation of character education based on tolerance among religious people conducted at Muhammadiyah Maumere High School. Data source obtained from primary data and secondary data. Primary data included informants which included the Principal, Deputy Principal for Student Affairs, Teachers (Islamic Religious Education, Catholicism, Citizenship), and Students. Data obtained from interviews with informants, observations and study documents. Data analysis techniques in this study began by reducing data, presenting data, and drawing conclusions. Testing the validity of the data using source triangulation techniques. The results obtained in this study indicate that the form of implementation of character education based on a tolerance between religious communities starts from the teacher implementing character education and applying tolerance values in the teaching and learning process of planning, implementation, and assessment, giving examples or examples to students in each learning process. Constraints faced are the lack of support and attention from parents, schools are less firm in applying and the lack of examples and support from teachers. Efforts made by the school are conducting religious activities and increasing extracurricular activities and conducting interpersonal communication.Keywords: Character Education, Tolerance, Religious harmony Abstrak:Penelitian ini bertujuan untuk mendeskripsikan implementasi pendidikan karakter berbasis toleransi antar umat beragama yang dilakukan di SMA Muhammadiyah Maumere. Penelitian ini merupakan jenis penelitian deskriptif kualitatif terhadap implementasi pendidikan karakter berbasis toleransi antar umat beragama yang dilakukan di SMA Muhammadiyah Maumere. Sumber datadiperoleh dari data primer dan data sekunder. Data primer ada informan yang meliputi Kepala Sekolah, Wakil Kepala Sekolah bidang Kesiswaan, Guru (Pendidikan Agama Islam, Agama Katolik, Kewarganegaraan), dan Siswa. Data diperoleh dari hasil wawancara dengan informan, observasi dan studi dokumen. Teknik analisis data dalam penelitian ini dimulai dengan mereduksi data, menyajikan data, dan menarik kesimpulan. Pengujian keabsahan data menggunakan teknik triangulasi sumber. Hasil penelitian yang diperoleh dalam penelitian ini menunjukkan bahwa bentuk implementasi pendidikan karakter berbasis toleransi antar umat beragama dimulai dari Guru mengimplementasikan pendidikan karakter dan menerapkan nilai toleransi dalam proses belajar mengajar dari perencanaan, pelaksanaan dan penilaian, memberikan teladan atau contoh kepada siswa dalam setiap proses pembelajaran. Kendala yang dihadapi yaitu kurangnya dukungan dan perhatian dari orangtua, sekolah kurang tegas menerapkan dan kurangnya contoh serta dukungan dari guru. Upaya yang dilakukan oleh sekolah yaitu melakukan kegiatan keagamaan dan meningkatkan kegiatan ekstrakurikuler dan melakukan komunikasi antar personal.Kata kunci: Pendidikan Karakter, Toleransi, Kerukunan Umat Beraga